Engineering Education in Wheeled Mobile Robotics. Issue 1 (July 2017) - Zdešar, Andrej; Blažic, Sašo; Klančar, Gregor
Abstract: This work describes educational approaches in the field of wheeled mobile robotics. On the case of an engineering course in masters study programme, we present how the course has evolved in the past few years to the current format. Our tendency is to organize the course lectures and laboratory practice in a way that an appropriate balance between the traditional and contemporary inductive learning and teaching methodologies is achieved. We present application of various inductive teaching methodologies, such as simulation challenges, individual projects, multi-team projects and competition challenges, to the course. Several project examples from the course are given.